PERAN KEPUASAN PELANGGAN SEBAGAI MEDIASI DALAM MENINGKATKAN LOYALITAS PELANGGAN - Tjahjaningsih, Endang; Sari, Diana Yunita (Jurnal Ilmiah Telaah Manajemen, 2019)
The phenomenon of the development of retail business types of supermarkets is becoming increasingly interesting because the fact is not all business people are able to survive optimally. To maintain survival, one way to do is always improve customer satisfaction. The purpose of this study is to develop and test the influence of company image and price perception in influencing satisfaction and its impact on customer loyalty, in order to win the supermarkets competition in Semarang. The sample used was 112 respondents at Giant Semarang Supermarket with a purposive sampling technique, showing data taken from specific targets. The results of the study resulted in a company's image and price perception positively affecting customer satisfaction and subsequently company image, price perception, and customer satisfaction positively affected customer loyalty. The results of the research prove the existence of a corporate image and the perception of image prices have a direct and indirect influence on loyalty by mediating by customer satisfaction, this shows that through corporate image and price perception can create satisfaction which will ultimately form customer loyalty. Keywords: company image, price perception, satisfaction and loyalty